High Intensity Training Program - Brzycki, M. (1994)
HIGH INTENSITY TRAINING I: This is the first of many installments pertaining to my experiences with and my understanding of what's become known as high intensity training or simply HIT. The first thing that must be understood is that HIT isn't something new--it's actually been around for decades. Years ago it wasn't called HIT--or anything else really--it was just a purposeful style of training that involved doing simple, basic exercises with aggressive, all-out levels of effort. (Even though it wasn't called HIT, I'll still refer to it as such for the sake of simplicity.) Anyway, HIT received a lot of attention--and created quite a controversial maelstrom--in 1970 with the publication of numerous articles written by Nautilus founder Arthur Jones. Although Jones didn't invent HIT, there's no question that he certainly was the one who popularized it and formally suggested guidelines and principles for its use. To some--including me--Jones was years ahead of his time and full of brilliant, revolutionary ideas about exercise; to others, he was the devil incarnate. One thing that everyone seems to agree upon was that he was abrasive, outspoken and brutally candid. Jones has mellowed with age but I got some laughs a few months ago when I saw him insult a group of unsuspecting sportsmedicine people with his trademark brash comments and demeanor. Anyway . . . In the early 1970s--back when there were still hippies--HIT meant relatively brief workouts (less than 1-1/2 hours; later less than 30 minutes), performed two or three times per week with a level of intensity that had to be seen to be believed. And what was seen was rarely a pretty sight. In fact, it was kinda ugly. Rarely were more than two sets of an exercise performed--and never more than three. You really couldn't do much more anyway. The level of intensity suggested by Jones was performing each exercise to the point of muscular failure. When you were done with an exercise, you moved your butt as fast as possible to the next exercise--which was already set up for you just waitin to be lifted. If you were to exhausted to walk--which was often the case--you crawled. If you were too exhausted to crawl--which was sometimes the case--you were physically grabbed and dragged to the next exercise. Jones' opinion of an acceptable level of intensity might best be summed up with one of his many colorful quotes: "Have you ever vomited as a result of doing one set of [bicep] curls? If not, then you simply don't know what hard work is." Ahh, those were the days.